Neural Network for Smart Adjustment of Industrial Camera - Study of Deployed Application - Doležel, Petr; Honc, Daniel (Springer, 2018)
Since machine vision is gaining more and more interest lately, it is necessary to deal with correct approaches to visual data acquisition in industry. As a particular part of this complex problematics, a technique for the industrial camera exposure time and image sensor gain tuning is presented in this contribution. In comparison to other approaches, a human expert photographer is used instead of explicitly defined cost function. His knowledge is transformed into an artificial expert system represented by a feedforward neural network. The expert system then provides the suitable exposure time and image sensor gain to gather sharp and balanced images.
Umělá neuronová síť pro nastavení parametrů průmyslové kamery
Keywords: industrial camera; smart camera; auto-exposure; artificial neural network; průmyslová kamera; chytrá kamera; umělá neuronová síť